Measurements of the partial pressure of CO2 in the air and surface sea water on board the icebreaker SHIRASE - Gen Hashida; Takakiyo Nakazawa; Shuhji Aoki; Shohei Murayama; Takashi Yamanouchi; Masayuki Tanaka; Akira Shimizu; Masahiko Hayashi; Kunimoto Iwai (National Institute of Polar Research, 1997)
With a newly developed automatic measurement system, the partial pressure of CO_2 in the surface sea water and lower troposphere were continuously monitored on board the icebreaker SHIRASE between Japan and Antarctica from November 1987 to March 1992 as a part of the Japanese Antarctic Research Expedition (JARE). The atmospheric CO_2 concentration was high in the midnorthern hemisphere, decreased rapidly southward to a minimum in the midsouthern hemisphere, and increased slightly in the Antarctic region. Water mass differences in the western North Pacific and eastern Indian Ocean can be seen in diagrams which consists of CO_2 partial pressure in surface sea water (pCO_2) and sea surface temperature (SST). These water masses are bordered at the boundaries of major oceanic currents : the southern border of the Kuroshio Countercurrent (28°N), the southern border of the Subtropical Countercurrent (20°N), the southern border of the North Equatorial Current (6°N), the southern border of the Celebes Sea, and the Lombok Strait. The relations between pCO_2 variations and hydrographic conditions such as the effect of coastal water and upwelling are subject to discussion in this report. Meridional distributions of pCO_2 and SST south of 35°S obtained in the southward cruise on 110°E in December, the northward cruise on 150°E in March, and the cruise between Syowa Station (69°00′S, 39°35′E) and Cape Town in January 1989 clearly show steep changes at the Subtropical Convergence, Subantarctic Front, and Polar Front. Even if pCO_2 within each water mass distributed between the fronts varies to some extent, each water mass can be distinguished from the other masses by the differences of average pCO_2 and SST. Longitudinal distributions of pCO_2 and SST measured in the westward track from 110°E to 20°E along 59°S to 61°S and the eastward track from 40°E to 150°E along 61°S to 65°S are scattered between 320μatm and 360μatm. However it is clearly evident that the pCO_2 dips by 50μatm between 80°E and 110°E. Anticyclonic eddies ...